Endothelial glycocalyx in hepatopulmonary syndrome: An indispensable player mediating vascular changes - Li, Liang; Cook, Christopher; Liu, Yale; Li, Jianzhong; Jiang, Jiantao; Li, Shaomin (Frontiers in Immunology, 2022)
Hepatopulmonary syndrome (HPS) is a serious pulmonary vascular complication that causes respiratory insufficiency in patients with chronic liver diseases. HPS is characterized by two central pathogenic features—intrapulmonary vascular dilatation (IPVD) and angiogenesis. Endothelial glycocalyx (eGCX) is a gel-like layer covering the luminal surface of blood vessels which is involved in a variety of physiological and pathophysiological processes including controlling vascular tone and angiogenesis. In terms of lung disorders, it has been well established that eGCX contributes to dysregulated vascular contraction and impaired blood-gas barrier and fluid clearance, and thus might underlie the pathogenesis of HPS. Additionally, pharmacological interventions targeting eGCX are dramatically on the rise. In this review, we aim to elucidate the potential role of eGCX in IPVD and angiogenesis and describe the possible degradation-reconstitution equilibrium of eGCX during HPS through a highlight of recent literature. These studies strongly underscore the therapeutic rationale in targeting eGCX for the treatment of HPS.